2011
DOI: 10.3389/fendo.2011.00101
|View full text |Cite
|
Sign up to set email alerts
|

Food Restriction-Induced Changes in Gonadotropin-Inhibiting Hormone Cells are Associated with Changes in Sexual Motivation and Food Hoarding, but not Sexual Performance and Food Intake

Abstract: We hypothesized that putative anorectic and orexigenic peptides control the motivation to engage in either ingestive or sex behaviors, and these peptides function to optimize reproductive success in environments where energy fluctuates. Here, the putative orexigenic peptide, gonadotropin-inhibiting hormone (GnIH, also known as RFamide-related peptide-3), and the putative anorectic hormones leptin, insulin, and estradiol were examined during the course of food restriction. Groups of female Syrian hamsters were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
56
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(60 citation statements)
references
References 120 publications
2
56
0
Order By: Relevance
“…In particular, RFRP-3 is commonly elevated during the nonbreeding season and suppressed following exposure to stimulatory photoperiods (brushtail possum: ref. 27 (31,32), with effects of social cues (i.e., nesting site availability) on GnIH activity also demonstrated in birds (33).…”
mentioning
confidence: 92%
“…In particular, RFRP-3 is commonly elevated during the nonbreeding season and suppressed following exposure to stimulatory photoperiods (brushtail possum: ref. 27 (31,32), with effects of social cues (i.e., nesting site availability) on GnIH activity also demonstrated in birds (33).…”
mentioning
confidence: 92%
“…Neuropeptide Y (NPY) is another neuropeptide that may be involved in transducing metabolic information to GnRH cells. The orexigenic role of NPY is well known (Bungo et al, 2011;Bechtold and Loudon, 2013;Davies and Deviche, 2015;Kuenzel et al, 1987;Richardson et al, 1995) and there are potential links between NPY cells and GnRH release (Contijoch et al, 1993;McShane et al, 1992) as well as between NPY and GnIH activity (Klingerman et al, 2011). The GnIH-NPY axis is thus hypothesized to play an important role in relating energy homeostasis to reproduction (Davies and Deviche, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Zebra finches do not show changes in hypothalamic GnIH immunoreactivity with changes in breeding status (Perfito et al, 2011). However, GnIH is sensitive to food restriction in birds and mammals (Klingerman et al, 2011;Fraley et al, 2013;Lynn et al, 2015), an environmental cue known to decrease reproduction in zebra finches. GnIH could act to transiently inhibit reproduction in times of stress or under poor breeding conditions (Perfito et al, 2011), supported by recent research in which food restriction was shown to affect the GnIH system (Lynn et al, 2015).…”
Section: Introductionmentioning
confidence: 96%